2022
DOI: 10.1155/2022/9042954
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Image under Artificial Intelligence Algorithm to Evaluate the Intervention Effect of Accelerated Rehabilitation Surgery Nursing on Laparoscopic Hysterectomy

Abstract: To explore the application value of accelerated rehabilitation surgery (ERAS) nursing in laparoscopic total hysterectomy, 120 patients who underwent laparoscopic total hysterectomy for benign uterine diseases in the hospital were selected as the research object. According to different nursing schemes, they were divided into 60 cases in the experimental group (ERAS nursing program) and 60 cases in the control group (traditional perioperative nursing). All patients underwent postoperative ultrasonography, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, this procedure also has significant disadvantages and is prone to post-operative complications such as incisional hernia and intestinal canal damage [11,12]. This study found that the study group experienced fewer hospitalization days and a lower frequency of post-operative complications than the control group, similar to the research by Li et al [7] and Yu et al [13]. These investigations revealed that under the nursing intervention model, the psychological, physical, and social care needs of elderly patients can be met, with patients' disease perceptions and their psychological status improving.…”
Section: Discussionsupporting
confidence: 87%
“…However, this procedure also has significant disadvantages and is prone to post-operative complications such as incisional hernia and intestinal canal damage [11,12]. This study found that the study group experienced fewer hospitalization days and a lower frequency of post-operative complications than the control group, similar to the research by Li et al [7] and Yu et al [13]. These investigations revealed that under the nursing intervention model, the psychological, physical, and social care needs of elderly patients can be met, with patients' disease perceptions and their psychological status improving.…”
Section: Discussionsupporting
confidence: 87%
“…Ultrasonic technique of the BCNN model based on deep learning is accurate for evaluating pelvic floor function. Yu et al [ 27 ] evaluated the effect of laparoscopic hysterectomy based on artificial intelligence imaging; ultrasound imaging based on ISCB algorithm can high-quality display the pelvic floor structure of patients undergoing total laparoscopic hysterectomy, improve the diagnostic rate of doctors, accelerate postoperative rehabilitation of patients, reduce postoperative pain, and improve patient satisfaction. In this experiment, BCNN-S had the highest accuracy of 88.98%; BCNN-R had the highest recall of 88.51%; and BCNN-R had the highest precision of 97.34%.…”
Section: Discussionmentioning
confidence: 99%
“…Among these methods, BCN-S had the highest accuracy of 88.98%, BCN-R had the highest recall rate of 88.51%, and BCN-R had the highest precision of 97.34%. Yin [32] et al showed that the pelvic floor mid-sagittal plane images processed by the artificial intelligence algorithm were clearerL the focus was more prominent, and the image quality was significantly improved. The Dice coefficient, positive predictive value, sensitivity, and Hausdorff distance of the algorithm were better than those of traditional algorithms.…”
Section: Advances In the Study Of Ai In Automated Aop Measurementmentioning
confidence: 99%